Efeito agudo de dois protocolos isométricos equalizados na relação esforço: pausa (work-to-rest ratio): respostas hemodinâmicas e autonômicas - Reis, Carlos Brendo Ferreira (2020)
Introduction: Little is known about the effects of distinct, equalized in work-to-rest (W:R) ratio set configuration on hemodynamic and autonomic response during and after acute strength training session. Objective: To analyze the acute effects of two iso